(untitled) (Journal of actual problems of jurisprudence, 2023)
In the modern period, as a result of the comprehensive development taking place in the international arena, there has been an increase in the number of hereditary relations of an international nature. Regulation of basic international hereditary relations deemed to be one of the urgent problems of our time. The reason for this problem is that the substantive rights of States in this area differ from each other. Studying the legislation of the world countries in the field of inheritance and conducting a comparative analysis, we observe significant differences, the absence of an international regulatory mechanism in this area or the presence of certain legal gaps. It is obvious that legislative acts in the field of regulation of these relations are different both in content and in form. There is no consensus on the statute of inheritance in international law. So, according to some approaches, the statute of inheritance refers to the constituent elements of this statute, or rather the circle of relations that it covers. These constituent elements have been defined in various forms in the substantive law of States. According to another approach, the statute of inheritance refers to the law that will apply to inheritance relations in general. This right is determined by means of the rules on conflict of laws. This opinion can be found in variety of literatures. Keywords: mandatory share, statute of inheritance, heirs, inheritance by law, inheritance by will